Innovation Management in Organizations and Their Industrial Classifications: An Approach to Building a New Typology - Arkady V. Trachuk; Natalia V. Linder (Communications of International Proceedings, 2022)
The article is devoted to the analysis of research in the field of typology and classification of innovations. We consider three types of classification the second innovation: the classification by type of innovation and application; classification of innovations by degree of novelty and level of change; rating by innovation. The article proposes a fourth approach to classifying innovations as possible to manage them. The signs of controllability for classification are highlighted: adaptability (level of use of innovation in various contexts), applicability (level of use of innovation in multiple settings), relatedness (connected with the main business of the innovator), architecture (shows how much innovation should be built into the system for application (or can be used independently without rebuilding the entire system as a whole), autonomy (to be able to use innovation regardless of other novelties), centeredness (reflects the level to which innovations can influence operations that are critical to organizational effectiveness), sociability (the degree to which individual aspects of innovation nations can be transferred to others to form a positive attitude towards its adoption) compatibility (the degree to which innovation is perceived as consistent with existing values, experience and the needs of potential followers). The types and classifications of product, technological (process), marketing, organizational and managerial innovations are examined. The so-called simulative innovations are separately considered. The analysis of the innovation activity of industrial companies made it possible to single out another new type - “value” innovations, which is the main theoretical contribution of this work.
Keywords: types of innovations; classification of innovations; Innovation Management; new typology